If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 2.49) = 3x Reorder the terms: 4(2.49 + x) = 3x (2.49 * 4 + x * 4) = 3x (9.96 + 4x) = 3x Solving 9.96 + 4x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 9.96 + 4x + -3x = 3x + -3x Combine like terms: 4x + -3x = 1x 9.96 + 1x = 3x + -3x Combine like terms: 3x + -3x = 0 9.96 + 1x = 0 Add '-9.96' to each side of the equation. 9.96 + -9.96 + 1x = 0 + -9.96 Combine like terms: 9.96 + -9.96 = 0.00 0.00 + 1x = 0 + -9.96 1x = 0 + -9.96 Combine like terms: 0 + -9.96 = -9.96 1x = -9.96 Divide each side by '1'. x = -9.96 Simplifying x = -9.96
| 5x+8=62-9x | | (x-4)(x+7)=x(2)-22 | | 2x+7=2(x-8) | | 105-6x=3x+6 | | 2x+6=21x-15 | | 0.18(y-3)+0.06y=0.14y-0.03(10) | | 8x+24=15x-70 | | 0.50x+0.10(130)=0.25(62) | | 0.70+0.20(70)=0.35(70) | | (-2)f-37=(-9) | | -3y-23=5y+17 | | 7x+3=-3+5x+16 | | 24-y=(-9) | | b^2+15b+54=0 | | 4(x+2)-8(3x+6)=9(4x+8) | | 8+-2(a+-1)=5+a | | 4*(x+2)-8*(3x+6)=9*(4x+8) | | 8-2(a-1)=5+9 | | 4x+16+40=160 | | 8-2(a-1)=7+9 | | 3+7n=31 | | 4p-10=-2p+14 | | 15-3n=9 | | 9p-7=4p+23 | | 11-2(9-1)=4+9 | | -5(x-2)=15 | | 5x+40=8x | | 5p+5=2p+20 | | -4(x-6)+7=31 | | 5*x+7=3*x+19 | | u^2-7u+6=0 | | 6*x-24=2*x |